1996
DOI: 10.1080/03610739608254006
|View full text |Cite
|
Sign up to set email alerts
|

Upright Standing and Gait: Are There Changes in Attentional Requirements Related to Normal Aging?

Abstract: This study evaluates attentional requirements for maintaining an upright posture and for walking among young and elderly persons to determine if, with normal aging, there is a deficit and/or a modification in the allocation of the attentional resources necessary for balance control. Eight young adults and 8 elderly persons were asked to respond to an auditory reaction time (RT) task (secondary task) while in a seated position, while in a broad-support or narrow-support upright standing position, and while walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
116
3
10

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(135 citation statements)
references
References 31 publications
6
116
3
10
Order By: Relevance
“…Previous studies have confirmed that locomotion is not traditionally considered to be automatic, but instead requires minimal attentional resources to maintain or regain gait stability (Lajoie et al 1993;Lajoie et al 1996;Ebersbach et al 1995;Sparrow et al 2002;Beauchet et al 2005). Increased attentional resources may be required while performing a more challenging task such as obstacle avoidance with a secondary task.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have confirmed that locomotion is not traditionally considered to be automatic, but instead requires minimal attentional resources to maintain or regain gait stability (Lajoie et al 1993;Lajoie et al 1996;Ebersbach et al 1995;Sparrow et al 2002;Beauchet et al 2005). Increased attentional resources may be required while performing a more challenging task such as obstacle avoidance with a secondary task.…”
Section: Discussionmentioning
confidence: 97%
“…A growing body of literature is showing that maintaining or regaining gait stability requires attentional resources, which provides additional evidence to support the concept that walking is not automatic but requires attentional resources (Lajoie et al 1993;Lajoie et al 1996;Sparrow et al 2002;Beauchet et al 2005). Attentional resources are assumed to be limited (Neumann 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some recent investigations provided evidence that the regulation of posture, from the simplest task (i.e., orthostatic) to the most complex one (i.e., unipodal balance), also involves attentional processes (Woollacott and Shumway-Cook 2002;Vuillerme and Nougier 2004). The mobilization of these attentional resources depends on (1) the age (Teasdale and Simoneau 2001;Woollacott and Shumway-Cook 2002), (2) the available sensory information (Shumway-Cook and Woollacott 2000; Teasdale and Simoneau 2001), (3) the postural task complexity (Lajoie et al 1996), (4) the expertise (Vuillerme and Nougier 2004), and (5) the voluntary attentional focus on body sway (Vuillerme and Nafati 2007). Indeed, these last authors observed a degradation of postural stability when it was asked to adult subjects to focus their attention on their posture.…”
Section: Introductionmentioning
confidence: 99%
“…Attention is defined as information processing capacity, space or resources of an individual 4,5) . Several studies [6][7][8] have shown that locomotion, although considered automatic, in fact requires some degree of attention. Furthermore, increased attention for standing and walking is required to compensate for age-related changes in the elderly, as compared to young adults.…”
Section: Introductionmentioning
confidence: 99%